Reevaluating the fraction of cancer attributable to excess weight: overcoming the hidden impact of prediagnostic weight loss - Safizadeh, Fatemeh; Mandić, Marko; Hoffmeister, Michael; Brenner, Hermann (European journal of epidemiology, 2024)
To evaluate the magnitude of the potential underestimation of the proportion of cancer cases attributable to excess weight, known as population attributable fraction (PAF), due to potential bias from prediagnostic weight loss already present at baseline of cohort studies and to overcome it as much as possible.
Gesehen am 25.02.2025